Factors of Civilizational Exchange Between Algeria and Tunisia in the Early 20th Century - Belkadi , Malika (The Algerian Historical Journal, 2026)
Algerian-Tunisian relations have historically been strong due to their geographical and cultural ties. Trade, politics, and intellectual exchanges have deeply influenced both nations. Their shared history fostered resistance to colonialism and the development of reform movements to preserve their identities. Arabic newspapers played a crucial role in strengthening their connections. Religious institutions like the University of Ez-Zitouna educated Algerian students. Sufi zawiyas provided both shelter and education. Trade routes and pilgrimages further encouraged cultural exchange. Intellectual movements from the Levant inspired their renaissance. Despite colonial efforts, these ties remained unbroken. Their relationship continues to be deeply rooted in history.